Efisiensi Teknis dan Faktor Penentu Inefisiensi pada Usahatani Jagung di Pamekasan Indonesia - Liniatil Hasanah; Elys Fauziyah; Isdiana Suprapti (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Maize is a strategic commodity due to its essential role in food, feed, energy, and industrial raw material supply. The significant role of maize has led to a continual increase in its demand each year. On the other hand, national maize production has declined, resulting in a portion of domestic demand being met through imports. A similar decline in maize production occurred in Larangan Luar Village, Pamekasan Regency. This study aims to analyze the factors influencing maize production, the level of technical efficiency, and the causes of inefficiency in maize farming in Larangan Luar Village. The research location was determined purposively, considering that the area is one of the maize production centers in Pamekasan. The sample consisted of 74 farmers, determined using the Slovin formula and selected through a random sampling method. The primary data used in this study were collected through interviews using a structured questionnaire. The research was conducted from September to December 2024. The research objectives were analyzed using the Cobb-Douglas Stochastic Frontier production function approach. Based on the analysis, variables that positively affect maize production are land area, seeds, and phonska fertilizer, while urea fertilizer has an adverse effect. The average level of technical efficiency among maize farmers is relatively low. The factors causing inefficiency are age and education. In light of the research findings, it is recommended that maize farmers adopt intercropping practices, enhance their knowledge of proper cultivation techniques, optimize the use of seeds and phonska fertilizer, and minimize reliance on urea fertilizer.